POPULATION DYNAMICS OF IRRIGATION FARMERS AND FISHERY FARMERS IN MUSI RAWAS DISTRICT - Hendra Gunawan; Muhammad Prima Cakra Randana (Socio-Economics/Agribusiness Department, 2023)
griculture has been recognized as an important sector in Indonesia. In addition to providing food and industrial raw materials, it contributes significantly to the growth of gross domestic product (GDP), foreign exchange, employment, and rural household income. One of the important triggers for the decline in harvested area and rice production in Musi Rawas Regency is the decline in rice field area due to the conversion of rice fields to non-rice fields. Conflicts over water resources vary from one area to another because water is not evenly distributed both in space and time. Therefore, this paper describes changes in the household population of rice farmers and changes in the population of aquaculture farmers in Musi Rawas Regency. This research was conducted using quantitative methods through a descriptive observational approach to secondary data obtained from the Government of Musi Rawas Regency, South Sumatra Province, Indonesia. The distribution of descriptive data was analyzed univariately using the SPSS Statistic 25.0 application. The area of rice fields increased from 2019 to 2021, followed by the number of farmers which also increased. The area of aquaculture is relatively stable in 2020 and 2021 and has increased compared to 2019. Meanwhile, aquaculture households from 2019 to 2021 continue to increase. he findings indicate the expansion of new rice fields (extensification) due to the need for new rice fields due to the increase in the population of farmers. The population of fish farmers is increasing even though the fishery area is constant. This condition indicates the fragmentation of fishery land.